PRONOUNS AND MODIFIERS IN APPLIED LINGUISTICS: A COMPREHENSIVE ANALYSIS (Modern education and development, 2024)
Pronouns and modifiers are essential components of language that contribute to sentence structure, meaning, and communication effectiveness. This article explores their roles within applied linguistics, emphasizing their sociolinguistic, pedagogical, and translational applications. The study discusses how these elements influence language acquisition, teaching, and cross-cultural communication while addressing common challenges encountered by learners and translators.